Evaluation of Tracking Algorithms for Automated Strain Analysis on Fascial Tissue - Halbe, Mirko; Wetter, Oliver Utz; Wallenstein, Torben; Schulze, Jan-Philipp; Höer, Jörg (2025 14th International Symposium on Image and Signal Processing and Analysis (ISPA))
This a secondary publication from 2026 of an original article published in *2025*. The development of detailed fascial tissue models is an essential aspect in research of medical suture failure. These models can be created on the basis of tensile test data and require accurate deformation measurement. Typically, this is done by applying colored dots or a speckle pattern to simplify the tracking with digital image correlation (DIC). This method leads to time-consuming preparation of the test objects and a computationally intensive analysis. This paper presents an alternative approach to automated strain analysis, using opensource tracking algorithms to measure the deformation of natural textures on fascial tissue. As part of the evaluation, a straindependent error in the displacement of individual tracking points was identified using artificial videos of idealized stretched fascial textures. By automating and simplifying the deformation measurement, the described approach enables researchers to easily investigate various different fascial tissue samples in order to generate more characteristic data and improve existing models
Keywords: Tensile test; fascial tissue analysis; texture tracking; OpenCV